What a Difference an OH Makes: Conformational Dynamics as the Basis for the Ligand Specificity of the Neomycin‐Sensing Riboswitch. Issue 4 (11th December 2015) - Duchardt‐Ferner, Elke; Gottstein‐Schmidtke, Sina R.; Weigand, Julia E.; Ohlenschläger, Oliver; Wurm, Jan‐Philip; Hammann, Christian; Suess, Beatrix; Wöhnert, Jens
Abstract: To ensure appropriate metabolic regulation, riboswitches must discriminate efficiently between their target ligands and chemically similar molecules that are also present in the cell. A remarkable example of efficient ligand discrimination is a synthetic neomycin‐sensing riboswitch. Paromomycin, which differs from neomycin only by the substitution of a single amino group with a hydroxy group, also binds but does not flip the riboswitch. Interestingly, the solution structures of the two riboswitch–ligand complexes are virtually identical. In this work, we demonstrate that the local loss of key intermolecular interactions at the substitution site is translated through a defined network of intramolecular interactions into global changes in RNA conformational dynamics. The remarkable specificity of this riboswitch is thus based on structural dynamics rather than static structural differences. In this respect, the neomycin riboswitch is a model for many of its natural counterparts. Abstract : Think local, act global : A synthetic neomycin riboswitch also binds paromomycin, which differs from neomycin only in the substitution of an amino group with a hydroxy group. Binding of paromomycin does not activate the switch, however, because the loss of key intermolecular interactions at one position of the paromomycin complex is translated through a defined network of intramolecular interactions into global changes in RNA conformational dynamics.